Solutions of the Quasilinear Elliptic Systems with Combined Critical Sobolev–Hardy Terms - Nyamoradi, N. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study the existence of multiple solutions for a quasilinear elliptic system. Based on the Ambrosetti–Rabinowitz mountain-pass theorem and the Rabinowitz symmetric mountain-pass theorem, we establish several existence and multiplicity results for the solutions and G-symmetric solutions under certain suitable conditions.